Poor clinical outcomes and immunoevasive contexture in CD161+CD8+ T cells barren human pancreatic cancer - Jun Yu; Liang Liu; Hanlin Yin; Qiangda Chen; Siyao Liu; Wenchuan Wu; Ning Pu; Wenhui Lou; Zhenlai Jiang; Taochen He; Yuqi Xie; Weilin Mao; et al. (Journal for ImmunoTherapy of Cancer)
Background The role of CD161 expression on CD8+ T cells in tumor immunology has been explored in a few studies, and the clinical significance of CD161+CD8+ T cells in pancreatic ductal adenocarcinoma (PDAC) remains unclear. This study seeks to clarify the prognostic value and molecular characteristics linked to CD161+CD8+ T cell infiltration in PDAC.Methods This study included 186 patients with confirmed PDAC histology after radical resection. CD161+CD8+ T cell infiltration was assessed using immunofluorescence staining on tumor microarrays. Flow cytometry and single-cell RNA sequencing were used to evaluate their functional status.Results We observed significant associations between tumor-infiltrating CD161+CD8+ T cells and clinicopathological factors, such as tumor differentiation, perineural invasion, and serum CA19-9 levels. Patients with higher tumor-infiltrating CD161+CD8+ T cell levels had longer overall survival (OS) and recurrence-free survival (RFS) than those with lower levels. Multivariable analysis confirmed tumor-infiltrating CD161+CD8+ T cell as an independent prognostic indicator for both OS and RFS. Notably, a combination of tumor-infiltrating CD161+CD8+ T cell and CA19-9 levels showed a superior power for survival prediction, and patients with low tumor-infiltrating CD161+CD8+ T cell and high CA19-9 levels had the worst survival. Furthermore, lower tumor-infiltrating CD161+CD8+ T cells were associated with a better response to adjuvant chemotherapy. Finally, we identified tumor-infiltrating CD161+CD8+ T cells as a unique subtype of responsive CD8+ T cells characterized by increased levels of cytotoxic cytokines and immune checkpoint molecules.Conclusion CD161+CD8+ T cells exhibit elevated levels of both cytotoxic and immune-checkpoint molecules, indicating as a potential and attractive target for immunotherapy. The tumor-infiltrating CD161+CD8+ T cell is a valuable and promising predictor for survival and therapeutic response to adjuvant chemotherapy in PDAC. Further research is warranted to validate its role in the risk stratification and optimization of therapeutic strategies.